«Allá es clínicamente así: saber llegar». De la formación a la práctica profesional médica. El Servicio Rural Urbano Marginal en Salud (SERUMS) - Reyes, Esperanza (2011)
The objective is to describe and discuss some findings on university education and learning of recent graduated doctors in their Rural and Marginal Urban Health Service (SERUMS) in the Junin region. Young doctors’ training is basically hospital based and their expectations after graduating are inclined to cure complex diseases rather than to develop primary health care activities. There is a recurrent lack of knowledge of management of health prevention and promotion programs in health posts and centers. How to communicate, give confidence, restore and support the decisions of patients are difficult in emergency situations or uncertainty about their illnesses. The emphasis on how to achieve humane care in which both professionals and patients can hear themselves and agree on joint decisions is a challenge in construction.